Parameters and Secondary Characters for Selection of Tolerance Rice Varieties under Stagnant Flooding Condition - Trias Sitaresmi; Willy B. Suwarno; Indrastuti A. Rumanti; Sintho W. Ardie; Hajrial Aswidinnoor (AGRIVITA, Journal of Agricultural Science, 2019)
Determination of secondary characters during stagnant flooding (SF) is considered important for breeders as the selection criteria in developing SF rice tolerant varieties. Aims of this study were to find agronomical variation and to determine secondary traits that were related to SF tolerance among the rice varieties. Experiment was conducted at Indonesian Center for Rice Research in 2015. Ten rice genotypes were grown in RCBD with three replications under normal and gradual flooding conditions. Agronomic data were gathered and analysed using combined ANOVA, correlation, multiple linear regressions and genetic variability. Results showed that 92.3% variance of stress tolerance index (STI) were presented from a linear model involving weight of 100-grains, panicle length, stem diameter, intensity of leaf green color and stem length. Stem length, intensity of leaf green color, and panicle length had broad genetic variability and high heritability these characters were important criteria when selecting the traits under flowing stress. Number of productive tillers was correlated with grain yield under SF and highly heritable, thus considered as one of determining characters for stagnant flooding tolerance. Based on STIStd, Ciherang and INPARI 30 showed more adaptive performance, while IR 42 had the least when grown under 50-60 cm stagnant water depth.